Analisis Perubahan Ritual Rebo Bontong Suku Sasak melalui Kepemimpinan Kiai Pesantren Darul Falah Mataram Lombok - Arifin, Muhamad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: An analysis of cultural changes in Rebo Bontong is carried out by implementing formulations, objectives, and strategies. In his formulation, the leadership of the Darul Falah Islamic Boarding School invites the community to be wise (bil ḥikmah) and make Rebo Bontong a rival. The objectives of holding Rebo Bontong rival cultural activities at Islamic boarding schools include: 1) amar ma'rūf nahi munkar 2) education of Ahlu al-Sunnah Wa al-Jamā'ah cadres. 3) momentum for students to learn and practice, 4) information to the public about the achievements and programs of the pesantren as well as asking for support from the community, 5) Building communication and relations with the community. While the change strategy goes through several processes, namely: 1) tazkiyatu al-nufus/cleansing the soul, 2) al-Tanshiat-al-Ijtima'iyah/introduction and outreach, 3) al-takwin/formation by making Rebo Bontong rivals, 4) al-tanfidz/routine the Rebo Bontong ritual, 5) al-istimrār/continuaity by instituting weekly, monthly, yearly programs.   Abstrak: Analisis terhadap perubahan budaya Rebo Bontong dilakukan dengan pelaksanaan rumusan, tujuan, dan strategi. Dalam rumusannya, Pimpinan Pesantren Darul Falah mengajak masyarakat secara bijaksana (bil ḥikmah) dan membuat Rebo Bontong tandingan. Adapun tujuan diadakannya kegiatan budaya Rebo Bontong tandingan di pesantren, antara lain adalah: 1) amar ma’ruf nahi munkar 2) pendidikan kader-kader Ahlu al-Sunnah Wa al-Jamā’ah. 3) momentum bagi santri untuk belajar dan berlatih, 4) informasi kepada masyarakat tentang capaian-capaian dan program-program pesantren sekaligus meminta dukungan kepada masyarakat, 5) Membangun komunikasi dan relasi dengan masyarakat. Sedangkan strategi perubahan nelalui beberapa peroses, yaitu: 1) al-tazkiyatu al-nufus/pembersihan jiwa, 2) al-Tanshiat-al-Ijtima’iyah/pengenalan dan sosialisasi, 3) al-takwin/pembentukan dengan membuat Rebo Bontong tandingan, 4) al-tanfidz/merutinkan ritual Rebo Bontong, 5) al-istimrār/keberlanjutan dengan melembagakan program mingguan, bulanan, tahunan.